2021
DOI: 10.3389/fonc.2020.621347
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary/Interstitial Applicator Plus Distal Parametrial Free Needle Interstitial Brachytherapy in Locally Advanced Cervical Cancer: A Dosimetric Study

Abstract: PurposeTo explore the dosimetric advantage of combining intracavitary/interstitial applicator with distal parametrial free needle interstitial brachytherapy (IC/IS+ISBT DP) based on MRI for locally advanced cervical cancer.Methods and Materials77 IC/IS+ISBT DP treatment plans were developed for 34 patients with locally advanced cervical cancer from June 2016 to January 2020 in this study. We removed the free needles and devised a new IC/ISBT treatment plan based on the same principle. We then compared the dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Similarly, a study by Qu et al (2021) [ 16 ] explored the dosimetric benefit of combining interstitial/intracavitary applicator with distant parametrial free needle interstitial brachytherapy according to the MRI for locally advanced cervical cancer. The study found that combining interstitial/intracavitary applicator with distant parametrial free needle interstitial brachytherapy provides an effective treatment for cervical cancer patients with distal parametrial extension [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study by Qu et al (2021) [ 16 ] explored the dosimetric benefit of combining interstitial/intracavitary applicator with distant parametrial free needle interstitial brachytherapy according to the MRI for locally advanced cervical cancer. The study found that combining interstitial/intracavitary applicator with distant parametrial free needle interstitial brachytherapy provides an effective treatment for cervical cancer patients with distal parametrial extension [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, a study by Qu et al (2021) [ 16 ] explored the dosimetric benefit of combining interstitial/intracavitary applicator with distant parametrial free needle interstitial brachytherapy according to the MRI for locally advanced cervical cancer. The study found that combining interstitial/intracavitary applicator with distant parametrial free needle interstitial brachytherapy provides an effective treatment for cervical cancer patients with distal parametrial extension [ 16 ]. Also, the results in Table 2 show that combining intracavitary and interstitial (IC-IS) BT provides a better outcome than using a single treatment approach, as the combination of the approaches was more conformal with minimal regular tissue exposure to intermediate doses [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study by Qu et al . [ 14 ], the mean depth of insertion of the distal parametrial needle was 6.52 ±2.8 cm, as it was done under ultrasound guidance. Moreover, Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…For FIGO stage IIIB-IVA patients with extensive parametrial and/or vaginal tumor extensions that cannot be covered adequately with IC-only BT, an important development was the addition of interstitial (IS) needles to further shape the dose asymmetrically, which has been shown to improve the therapeutic ratio [ 15 , 16 ]. Earlier combined IC/IS techniques involved either trans-perineal or trans-vaginal free-hand implantation of metallic needles, which required considerable skills from the radiation oncologist to accurately reach the target [ 17 ]. This has led to the development of combined IC/IS applicators that use the IC vaginal component as a template to guide straight needles made of either metal or less invasive plastic.…”
Section: Purposementioning
confidence: 99%